If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 15 = 11x + 14 Reorder the terms: 15 + 10x = 11x + 14 Reorder the terms: 15 + 10x = 14 + 11x Solving 15 + 10x = 14 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 15 + 10x + -11x = 14 + 11x + -11x Combine like terms: 10x + -11x = -1x 15 + -1x = 14 + 11x + -11x Combine like terms: 11x + -11x = 0 15 + -1x = 14 + 0 15 + -1x = 14 Add '-15' to each side of the equation. 15 + -15 + -1x = 14 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 14 + -15 -1x = 14 + -15 Combine like terms: 14 + -15 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 9(13t+11)= | | 10=5/3v | | 175m-75m+48000=51000-150m | | 12/20=3/5 | | 8(13+15B)= | | 30x+10(100-x)=180 | | 5/2y=40 | | 12(11r-10)= | | 4y+2z-x= | | 16t^2+8t-80=0 | | 3(9a-6)= | | 5(8b+10)= | | -(6x-(2x+9))=-4-(6(2x-4)-6x) | | 7(5+y)= | | 25/60=5/15 | | 1.2x+3.8=8.696 | | 4(c-9)=-24 | | Q=1640-20p | | 10x+9=2x+25 | | 37x+5=y | | q+72=36 | | -y=5x+7 | | 2/5x-12/5 | | x+2x+3x-3-8=6x-11 | | 5(3h+-2)=2(h+8) | | -108+72=36 | | 110=(5a+6a) | | X-18=11x-38 | | 8(6u+5)= | | 6(2+a)=-18 | | 45=9q | | 25x^9/5x^8 |